2017
DOI: 10.1002/joc.5182
|View full text |Cite
|
Sign up to set email alerts
|

Offshore wind climate analysis and variability in the Mediterranean Sea

Abstract: ABSTRACT:The long-term offshore wind characteristics in the Mediterranean Sea are assessed using the ERA-Interim dataset for the period 1979-2014. Three main aspects of the wind climate analysis are examined in detail; the spatio-temporal behaviour (including variability characteristics) of wind speed and direction for the annual and monthly time scale; the joint association of wind speed and direction for the annual and monthly time scale, and; the wind speed trends and wind direction changes. From this analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 97 publications
(119 reference statements)
11
35
0
Order By: Relevance
“…To give some examples of recent observational studies, wind speeds have shown a negative trend in Finland (years 1959-2015) throughout the year (Laapas and Venäläinen 2017) and in southwestern Germany (years 1974-2013) in spring and summer (Kohler et al 2018). In the Mediterranean area during 1979-2014, by contrast, the observational trends have been spatially divergent (Soukissian et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To give some examples of recent observational studies, wind speeds have shown a negative trend in Finland (years 1959-2015) throughout the year (Laapas and Venäläinen 2017) and in southwestern Germany (years 1974-2013) in spring and summer (Kohler et al 2018). In the Mediterranean area during 1979-2014, by contrast, the observational trends have been spatially divergent (Soukissian et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The highest inter-annual variability appears near the coasts of Monaco and then in the northern Adriatic, Tyrrhenian, and Balearic Seas; the Gulf of Lion; the coasts of Algeria; and the Ionian and the central Aegean Sea. Recently, an in-depth assessment of the wind climate and its variability in the MS is analytically presented, using a 36-year dataset (1979-2014) from the ERA-Interim reanalysis [106]. The data were available from the European Centre For Medium-Range Weather Forecasts (ECMWF).…”
Section: Wind and Wave Climatementioning
confidence: 99%
“…As anemophilous species, wind strength and direction during flowering time would determine pollen flow patterns in P. lentiscus . The prevailing winds in the Mediterranean Basin flow from the Northwest to the Southeast from March to May with a greater angular variance in the western than in the eastern regions (Soukissian, Karathanasi, Axaopoulos, Voukouvalas, & Kotroni, 2018). Even though pollen flow might account for low genetic distances among some populations at both shores of the Mediterranean Sea (e.g., Iberian Peninsula and Balearic populations), it does not explain the observed patterns for other populations (e.g., low genetic distance among Aegean and Libyan populations).…”
Section: Discussionmentioning
confidence: 99%